Genetic reporter analysis reveals an expandable reservoir of OCT4+ cells in adult skin - Limbourg, Anne; Schnabel, Sabine; Lozanovski, Vladimir J.; Napp, L Christian; Ha, Teng-Cheong; Maetzig, Tobias; Bauersachs, Johann; Naim, Hassan Y; Schambach, Axel; Limbourg, Florian P (Cell Regeneration, 2014)
The transcription factor Oct4 (Pou5f1) is a critical regulator of pluripotency in embryonic and induced pluripotent stem cells. Therefore, Oct4 expression might identify somatic stem cell populations with inherent multipotent potential or a propensity for facilitated reprogramming. However, analysis of Oct4 expression is confounded by Oct4 pseudogenes or non-pluripotency-related isoforms. Systematic analysis of a transgenic Oct4-EGFP reporter mouse identified testis and skin as two principle sources of Oct4+ cells in postnatal mice. While the prevalence of GFP+ cells in testis rapidly declined with age, the skin-resident GFP+ population expanded in a cyclical fashion. These cells were identified as epidermal stem cells dwelling in the stem cell niche of the hair follicle, which endogenously expressed all principle reprogramming factors at low levels. Interestingly, skin wounding or non-traumatic hair removal robustly expanded the GFP+ epidermal cell pool not only locally, but also in uninjured skin areas, demonstrating the existence of a systemic response. Thus, the epithelial stem cell niche of the hair follicle harbors an expandable pool of Oct4+ stem cells, which might be useful for therapeutic cell transfer or facilitated reprogramming.